Transformasi Identitas: Australia dari Era Immigration Resstiction Act 1901 Menuju Masa Multikultural - Dita Amalia; Ribawati, Eko (Multikultural: Jurnal Ilmu Sosial, 2024)
In this study, the researcher wants to describe several developments that occurred in Australia during the implementation of the Immigration Restriction Act policy and the existence of multicultural policies that influenced the challenges of Australian social life at that time. The method used is qualitative through historical research using library research as a search for sources and information. The results of this research show that Australia is an immigration country, where Australia is one of the countries that needs a lot of labor, but in contrast, the population of Australia itself is very small and in addition, it lost its population due to participation in World War II (Pacific). If Australia implements the Immigration Restriction Act, it is very unsuitable because it limits immigration movements, especially for Asians, who incidentally are more numerous than Europeans. Therefore, to develop its country, Australia must understand and accept cultures from various national backgrounds by transforming its identity from monocultural to multicultural. So a multicultural policy is needed by Australia to eliminate acts of discrimination due to the Immigration Restriction Act policy